Effect-detection by planar SOS-Umu-C genotoxicity bioassay and chemical identification of genotoxins in packaging migrates, proven by microtiter plate assays SOS-Umu-C and Ames-MPF. (May 2023) - Meyer, Daniel; Marin-Kuan, Maricel; Mayrhofer, Elisa; Kirchnawy, Christian; Debon, Emma; Latado, Helia; Patin, Amaury; Schilter, Benoît; Morlock, Gertrud
Abstract: Recently shown to meet regulatory requirements for safety assessment, high-performance thin-layer chromatography hyphenated with the SOS-Umu-C bioassay and S9 metabolization was applied to various food contact material prototypes, such as paper, plastic and coating samples. Studying reversed versus normal phase separation and piezoelectrical spraying versus syringe dosage of the bioassay, 14 genotoxic bands were detected. Three epoxides of linolenic acid were identified as genotoxic candidates in the paper migrate by heated electrospray and atmospheric pressure chemical ionization high-resolution mass spectrometry. These were confirmed by co-chromatography with linolenic acid epoxides. Comparatively poorer detection limits of in vitro microtiter plate bioassays and opposing effects/signal responses in the sample explained false-negative responses for paper migrate. However, the in vitro SOS-Umu-C microtiter plate bioassay confirmed the genotoxicity of a simulated linolenic acid epoxidation, and after sample concentration, the paper migrate mutagenicity was confirmed by the Ames-MPF™ bioassay. Highlights: On-surface metabolic activation via S9 system studied by piezoelectric spraying. Assay application investigated via two techniques (ChromaJet versus Derivatizer). Genotoxic compounds detected in migrates of packaging material. Genotoxic epoxides of linolenic acid identified in paper migrate. NP/RP-HPTLC−Vis/FLD−(S9)–SOS-Umu-C bioassay and −APCI/HESI-HRMS.